1954
DOI: 10.2136/sssaj1954.03615995001800030008x
|View full text |Cite
|
Sign up to set email alerts
|

Some Factors Affecting the Adsorption of Sulfate by Alabama Soils

Abstract: The sulfate content of a number of Alabama Soils was determined by extracting with various solutions. The sulfate extracted was measured turbidimetrically. Some factors affecting the adsorption of sulfate by soils were studied. About the same amount of sulfate was extracted by neutral sodium acetate solution, sodium acetate buffered at pH 4.8, KH2PO4 solution containing 100 ppm. phosphorus, and KH2PO4 solution containing 500 ppm. phosphorus. However, 0.1 N HCl solution extracted little or no sulfate. The sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0
10

Year Published

1958
1958
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(100 citation statements)
references
References 0 publications
2
88
0
10
Order By: Relevance
“…The adsorbed SO^^' fraction can be extracted from soils by a variety of extractants. These include Ca(H2P04)2 (Fox et al, 1964), KHgPO^ (Ensminger, 1954), Ca(0H)2 and CaCOg suspensions (Williams and Steinberg, 1962), NaHCOg (Kilmer and Nearpass, 1960), neutral 1 N NH4OAC (McClung et al, 1959), acid NH^OAc (Bardsley and Lancaster, 1960;Sanford and Lancaster, 1962), and Morgan's solution (Chesnin and Yien, 1950). Fox et al (1964) found Ca(H2P04)2 to be preferable to KH2PO4 because, while it gave values similar to KH2PO4, it also produced extracts essentially free of colloidal material which is often a problem with KH2PO4.…”
Section: Inorganic Forms Of Sulfurmentioning
confidence: 99%
“…The adsorbed SO^^' fraction can be extracted from soils by a variety of extractants. These include Ca(H2P04)2 (Fox et al, 1964), KHgPO^ (Ensminger, 1954), Ca(0H)2 and CaCOg suspensions (Williams and Steinberg, 1962), NaHCOg (Kilmer and Nearpass, 1960), neutral 1 N NH4OAC (McClung et al, 1959), acid NH^OAc (Bardsley and Lancaster, 1960;Sanford and Lancaster, 1962), and Morgan's solution (Chesnin and Yien, 1950). Fox et al (1964) found Ca(H2P04)2 to be preferable to KH2PO4 because, while it gave values similar to KH2PO4, it also produced extracts essentially free of colloidal material which is often a problem with KH2PO4.…”
Section: Inorganic Forms Of Sulfurmentioning
confidence: 99%
“…P adjusted to pH 6.5) as recommended by Ensminger (1954 Sulphate soluble in 0.15% CaCl 2 after heat treatment ("heat-treated" soluble sulphate) is that fraction representing easily mineralisable sulphur and is measured by determining the soluble sulphate present after pre-treatment of the moist soil on a hot-water bath (Williams and Steinbergs 1959).…”
Section: Chemical Analysesmentioning
confidence: 99%
“…No entanto, a disponibilidade imediata do S é controlada pelo processo de adsorção/dessorção do sulfato, por meio do equilíbrio rápido entre aquele que está na solução e aquele da fase sólida do solo. A adsorção do sulfato depende principalmente dos teores e dos tipos de argilominerais e de óxidos presentes no solo, e os grupos funcionais das arestas quebradas da caulinita e aqueles da superfície dos óxidos de ferro são os que possuem maior capacidade de reter esse íon (Ensminger, 1954;Peak et al, 1999). O pH do solo, por sua vez, interfere na energia de ligação dos grupos funcionais aos cátions metálicos estruturais dos argilominerais e óxidos do solo, e seu aumento causa sua desprotonação, dificultando e até impedindo a adsorção de sulfato (Mehlich, 1964;Parfitt e Smartt, 1978;Peak et al, 1999;Casagrande et al, 2003;Goldberg, 2010).…”
Section: Introductionunclassified